2019
DOI: 10.1080/24699322.2019.1649078
|View full text |Cite
|
Sign up to set email alerts
|

Novel joint algorithm based on EEG in complex scenarios

Abstract: At present, in the field of electroencephalogram (EEG) signal recognition, the classification and recognition in complex scenarios with more categories of EEG signals have gained more attention. Based on the joint fast Fourier transform (FFT) and support vector machine (SVM) methods, this study proposed a novel EEG signal-processing joint method for the complex scenarios with 10 classifications of EEG signals. Moreover, a comprehensive efficiency formula was put forward. The formula considered the accuracy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(38 reference statements)
0
8
1
Order By: Relevance
“…Other than that, EPOC has 14 channels, and Muse only four channels that make the comparison is not fair. Also, the research found here has lower accuracy with the research report in [6]. This might be happened because of the difference in the data and also the way of testing that is used.…”
Section: Figure 11 Paired Wilcoxon Rank Resultscontrasting
confidence: 65%
See 4 more Smart Citations
“…Other than that, EPOC has 14 channels, and Muse only four channels that make the comparison is not fair. Also, the research found here has lower accuracy with the research report in [6]. This might be happened because of the difference in the data and also the way of testing that is used.…”
Section: Figure 11 Paired Wilcoxon Rank Resultscontrasting
confidence: 65%
“…Compared with the result found in [2] and [7], this experiment with frequency band produces a competitive result. Otherwise, compared to [6] the accuracy in this experiment is lower. This might happen because of the data difference and the technique to do the testing.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations